Stečkin inequalities for summability methods - Jia-Ding Cao (International Journal of Mathematics and Mathematical Sciences)
Stečkin proved an inequality on Fejér means of Fourier series He said, Proving similar inequality for other summability method is an interesting problem. We generalize Stečkin's inequality and give various applications to summability methods.